2016
DOI: 10.18666/jasm-2016-v8-i2-6444
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Team Identification and Gender on Rival Perceptions and Consumption Intentions of Intercollegiate Athletics Fans

Abstract: The current study investigated rival perceptions using the Sport Rivalry Fan Perception Scale (SRFPS) (Havard, Gray, Gould, Sharp, & Schaffer, 2013) on a group of male and female intercollegiate athletics fans at various levels of favorite team identification. To this point, the SRFPS has primarily been used to examine highly identified male fans (Havard, Reams, & Gray, 2013;Havard, Wann, & Ryan, 2013). The current study extended previous research on rivalry by finding that rival perceptions were impacted by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Further, Kilduff et al (2010) suggest that rivalry is driven more by long-term than short-term competition. Based on Social Identity Theory (Tajfel, 1974), research on rivalry has focused on the influence the phenomenon has on individual sport fans and fan groups (Dalakas & Melancon, 2012;Dalakas, Melancon, & Sreboth, 2015;Havard, 2014Havard, , 2016Havard, Eddy, & Ryan, 2016;Havard & Reams, 2016;Havard, Shapiro, & Ridinger, 2016). Because competitive history is so important to the formation and existence of rivalry, the recent bevy of schools that changed athletic conferences would fundamentally alter teams seen as rivals to fan groups.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Further, Kilduff et al (2010) suggest that rivalry is driven more by long-term than short-term competition. Based on Social Identity Theory (Tajfel, 1974), research on rivalry has focused on the influence the phenomenon has on individual sport fans and fan groups (Dalakas & Melancon, 2012;Dalakas, Melancon, & Sreboth, 2015;Havard, 2014Havard, , 2016Havard, Eddy, & Ryan, 2016;Havard & Reams, 2016;Havard, Shapiro, & Ridinger, 2016). Because competitive history is so important to the formation and existence of rivalry, the recent bevy of schools that changed athletic conferences would fundamentally alter teams seen as rivals to fan groups.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Only those who were at least 18 years old, U.S. residents, and self-identified as MLB fans from a menu of professional and collegiate U.S. sports were targeted. Prior sport management research measuring behaviors and intentions across differently identified sport consumers has found MTurk to be an advantageous crowdsourcing approach to participant recruitment [85][86][87]. Likewise, previous climate change and climate risk research has also relied on MTurk samples despite potential validity concerns [88][89][90].…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Sports fandom has been studied for many years, with a strong focus on sport consumer loyalty and fan team identification analyzed from the perspective of psychology, sociology and sports marketing, management, economics, and consumer behavior (Bodet & Bernache-Assollant, 2011;Melnick & Wann, 2004Theodorakis & Wann, 2008;Wann et al, 2001Wann et al, , 2021. Less attention has been paid to female fandom and women's sport in sports media but this gap in research has been also already increasingly filled (e.g., Dietz-Uhler et al, 2000;Farrell et al, 2011;Gemar & Pope, 2022;Havard et al, 2016;Koch & Wann, 2016;Kossakowski et al, 2022;Organista et al, 2021;Ridinger & Funk, 2006), and less involved sport fans, in other words, sport consumers, their mundane sport-related consumer practices (Crawford, 2003;Gemar, 2020) and changing their styles of media use (e.g., Chan-Olmsted & Xiao, 2019).…”
Section: Introductionmentioning
confidence: 99%